Mapping Route Overlaps and Untapped Demand: A Spatial Optimization Study of TransJakarta’s Multimodal Network (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
This study examines the spatial efficiency of TransJakarta’s multimodal public transport network by analyzing route overlaps, passenger mobility patterns, and underserved high-density areas across Jakarta. Using a mixed-methods approach that combines passenger survey data, descriptive statistics, and GIS-based spatial modeling, the study evaluates 234 routes serving more than 96 million passengers between January and May 2023. Intersect geoprocessing reveals 34 overlapping routes, with three Mikrotrans services—JAK 120, Mikrotrans 13, and JAK 22—performing poorly despite running parallel to BRT and Non-BRT corridors with moderate to high ridership. These redundancies contribute to congestion, inefficient fleet utilization, and unnecessary subsidy expenditures. Desire line analysis further shows that commuter flows are highly concentrated in central Jakarta, yet several high-population kelurahan such as Tambora and Cipayung remain underserved by Non-BRT and Mikrotrans coverage. Findings highlight a significant mismatch between network supply and actual mobility needs, rooted in limited use of OD-based planning and fragmented coordination among service providers. The study underscores the need for data-driven route restructuring, the reduction of redundant services, and strategic expansion into high-demand areas to improve accessibility and support a more sustainable urban mobility system